The Effect of an Exhaustive Aerobic, Anaerobic and Resistance Exercise on Serotonin, Beta-endorphin and BDNF in Students - M. Sharifi; M.R. Hamedinia; S.A. Hosseini-Kakhak (Physical Education of Students, 2018)
Background and Study Aim: Sport exercises play a major role in many hormonal factors which related to happiness in human. Therefore, the short-term effects of three anaerobic, aerobic and resistance exercises on (BDNF) and hormones related to happiness such as serotonin and beta-endorphin has been studied in young men in this research. Materials and Methods: Thirty-two students (19 to 25 years old) who did not have regular physical activity were randomly divided into four groups, after the subjects were eaten the same breakfast, the blood of them were taken before and after the various short aerobic exercises (Exhaustive exercise with 70% of maximum heart rate) and anaerobic (Exhaustive exercise with maximum intensity) and exhaustive resistance exercise (with 8 stations). Control group did not practice any activity. Specific kits and ELISA method have been used to determine their values. Data were analyzed using ANOVAand ANCOVA method at a significant level of 5%. Results: Beta-endorphins showed a significant increase in resistance and aerobic training sessions compared to control group. However, serotonin and BDNF had a significant intra-group change in the aerobic group. Conclusion: It seems that aerobic exercises are the best practice for increasing some of the hormones associated with happiness.